(untitled) (Clinics, 2013)
OBJECTIVE: Available chemotherapy presents poor control over the development of metastatic melanoma. FTY720 is a compound already approved by the Food and Drug Administration for the treatment of patients with multiple sclerosis. It has also been observed that FTY720 inhibits tumor growth in vivo (experimental models) and in vitro (animal and human tumor cells). The aim of this study was to evaluate the effects of FTY720 on a metastatic melanoma model and in tumor cell lines. METHODS: We analyzed FTY720 efficacy in vivo in a syngeneic murine metastatic melanoma model, in which we injected tumor cells intravenously into C57BL/6 mice and then treated the mice orally with the compound for 7 days. We also treated mice and human tumor cell lines with FTY720 in vitro, and cell viability and death pathways were analyzed. RESULTS: FTY720 treatment limited metastatic melanoma growth in vivo and promoted a dose-dependent decrease in the viability of murine and human tumor cells in vitro. Melanoma cells treated with FTY720 exhibited characteristics of programmed cell death, reactive oxygen species generation, and increased β-catenin expression. In addition, FTY720 treatment resulted in an immunomodulatory effect in vivo by decreasing the percentage of Foxp3+ cells, without interfering with CD8+ T cells or lymphocyte-producing interferon-gamma. CONCLUSION: Further studies are needed using FTY720 as a monotherapy or in combined therapy, as different types of cancer cells would require a variety of signaling pathways to be extinguished.